Islamic Corporate Governance Based On Sharia Enterprise Theory Grounded In Nubuwwah Morals - Anwari, Moh. Anis; Dzikrulloh , Dzikrulloh (LP2M IAI Miftahul Ulum Pamekasan, 2023)
The purpose of this paper is to review some writings about corporate governance in Islamic perspective. The author also tried to contribute thoughts to enrich the theory of Islamic corporate governance, namely GCG based shariati enterprise theori based nubuwwah morals. The writing method used is qualitative research with a literature review approach. This research began by exploring scientific studies of Islamic corporate governance and ended by offering a new approach to thinking on GCG theory. Corporate governance mechanisms in Shariati-based Islamic enterprise theori more see corporate control as self-control with the principle of Tawhid carried out by individuals and corporate organizations by sticking to improving the quality of individual and social piety. The concept of moral nubuwwah helps the company always carry out the company's activities by prioritizing humanist, transcendental and teleological character.